Preliminary evidence for the factor structure, concurrent validity, and construct validity of the Roommate Relationship Scale in a college sample - Willis, Mairéad A.; Lane, Sean P. (Frontiers in Psychology, 2022)
Roommate relationships are fundamental to the social environment of many emerging adults. However, no validated, widely used, measure of roommate relationship quality exists for examining the impact of these relationships on individual functioning and health. In this report, we present preliminary evidence of the factor structure, concurrent validity, and construct validity of the roommate relationship scale (RRS) as a measure of roommate relationship quality using a sample of U.S. college students who participated in a multi-wave study. An exploratory factor analysis at the first wave, and confirmatory factor analyses (CFAs) with independent samples of new participants at each of two subsequent waves showed stable factor loadings and adequate fit. Moreover, the scale demonstrated good fit and reliability in a more sophisticated, longitudinal multilevel CFA framework. The RRS significantly positively correlated with relationship length, self-esteem, extraversion, agreeableness, and conscientiousness, and negatively correlated with symptoms of anxiety and avoidant attachment style, indicating concurrent validity of the scale with respect to these constructs. Consistent with findings from other relationship types, self-reported RRS scores decrease longitudinally, both across and between semesters of academic life, indicating construct validity of the scale. We conclude that the RRS is useful for evaluating roommate relationship quality among U.S. college students, and hopefully beyond. Further research should validate the scale’s utility in other, more diverse, populations and refine its underlying generating psychological process.